Implementasi Program Baca Tulis dan Hafal Al-Qur’an dalam Meningkatkan Literasi Al-Qur’an Siswa di SMP Muhammadiyah 2 Kota Tegal - Arief Mushoffa Gymnastiar; Suwito Suwito (Yayasan Pendidikan Penelitian Pengabdian Algero, 2025)
The low ability to read and write the Qur’an among the younger generation remains a serious challenge, as many Muslims in Indonesia still struggle with these skills. To respond, SMP Muhammadiyah 2 Kota Tegal introduced the Qur’an Reading, Writing, and Memorization (BTHQ) program to strengthen Qur’anic education in formal schools. This study aims to analyze the implementation of the program and evaluate its effectiveness in improving students’ Qur’anic literacy through a qualitative case study, using data from observations, interviews, and documentation, which were analyzed with the Miles and Huberman model and validated through triangulation. The findings reveal that the program is supported by competent teachers, though limited by the number of instructors, facilities, and time allocation. Results from the assessment instrument developed by the researcher show that most students achieved “very good” and “good” categories, especially in reading and memorization. The study’s novelty lies in designing a more comprehensive assessment tool and applying Van Meter and Van Horn’s policy implementation theory, offering a new perspective on evaluating the effectiveness of Qur’anic education in schools.